The quality of equality: thinking differently about gender inclusion in organizations - Adamson, M.; Kelan, Elisabeth K.; Lewis, P.; Rumens, N.; Śliwa, M. (Emerald, 2016)
Purpose This paper aims to suggest a shift in thinking about how to improve gender inclusion in organizations, as well as offering a number of practical action points. - Design/methodology/approach This paper takes a perspective based on the authors’ own ongoing research, as well as synthesis of existing insights into gender inclusion in organizations. - Findings To retain top talent and improve organizational climate, the authors need to re-think how the authors measure the success of organizational inclusion policies. Specifically, the paper suggests moving from numbers and targets to looking at the quality of gender inclusion in the workplace. The paper explains why this shift in thinking is important and how to approach it in practice. - Practical implications The paper provides strategic insights into and practical thinking about ways in which progressive organizations can continue to improve gender equality. - Originality/value The paper makes a provocative call for a change of perspective on gender inclusion in organizations based on cutting-edge research and puts forward action points in an accessible format.
Keywords: Gender; Inclusion; equal opportunities; gender equality strategy; HR policy; Women in organizations